Arterial Tortuosity Syndrome reveals function of dehydroascorbic acid in collagen and elastin synthesis: Implications for skin care. (February 2016) - Kitt, Douglas Q.
Abstract: Some investigations in Arterial Tortuosity Syndrome (ATS) suggest that impaired intracellular transport of the oxidized form of vitamin C (dehydroascorbic acid, DHAA) is at the core of the pathogenesis. Lack of vitamin C for lysyl- and prolyl-hydroxylase activity may explain the defects in collagen and elastin formation found in ATS, and draws strong parallels between ATS and scurvy. Topically applied vitamin C has a well-established basis in the field of skin care, and part of its benefit is attributed to proper collagen formation in the skin. The ATS studies suggest that DHAA transport is necessary for normal skin collagen formation, and this has implications as to the forms of vitamin C best-suited for topical skin care.